Knowledge and Awareness of Masks and N95 Respirators Used for COVID-19 Prevention Among Chemical Engineering Students at Al-Balqa Applied University, Jordan - Hudaib, Banan; Al-shawabkeh, Ali F.; Hudaib, Fadia (Frontiers in Public Health, 2022)
Background and Objectives: On March 11, the World Health Organization stated coronavirus disease 2019 (COVID-19) was a global pandemic; the rapid and extended spread of the COVID-19 pandemic has become a significant cause of concern for face-to-face university study. This study investigated the knowledge and awareness of chemical engineering students in Al-Balqa Applied University (BAU) in Jordan about respiratory protective measures against COVID-19. Materials and Methods: A cross-sectional study was developed using a multi-stage random sampling technique conducted from April 21–28, 2020. The data were collected through an online questionnaire distributed to BAU's chemical engineering students, with 179 responders completed the survey correctly. The data were analyzed statistically using the SPSS program. The questionnaire consisted of two parts: the first measured the student's general knowledge about the COVID-19 pandemic, while the second focused on the respiratory protection methods against COVID-19; it was structured to assess the student's knowledge about the suitable types of masks and respirators used in COVID-19 prevention, their detailed mechanism of action and filtration process type, their production materials, and finally how the student's knowledge affects choosing a proper preventive method. Results: The study found moderate awareness among engineering students about COVID-19 causative agent, effective preventive masks/respirators used, and the mask's viral blockage mechanisms. A total of 89 respondents (49.7%) pointed to the correct best protective mask, i.e., N95 mask. On the other hand, 119 respondents (66.5%) believed that a surgical mask is the best protective mask. The study also showed differences in knowledge between different academic years; the knowledge about respirators, masks, and their action mechanism among senior students in the last three academic years was better than the younger students with a P-value of 0.047 for knowledge about respirator used for protection against coronavirus disease and the P-value of 0.028 for knowledge of the comparisons between the N95 and surgical mask. On the other hand, the study showed a lack of awareness of the most suitable mask types used in pandemics and the appropriate use method. Conclusions: The study found that chemical engineering students in Al-Balqa university were moderately knowledgeable regarding COVID-19 respiratory preventive methods; these results provided an overview of each student's community's knowledge level. Therefore, efforts are needed to improve public awareness through comprehensive educational campaigns to increase students' knowledge, attitude, and practice.